Eco-friendly processing in enzymatic xylooligosaccharides production from corncob: Influence of pretreatment with sonocatalytic-synergistic Fenton reaction and its antioxidant potentials - Kawee-Ai A. (2017)
© 2015 Elsevier B.V. All rights reserved. Delignification can be considered as a feasible process to pretreat lignocellulosic biomass in xylooligosaccharides production after the performance and efficiency has been improved through a few modifications. This study compared various pretreatment strategies such as Fenton, sonocatalytic, and sonocatalytic-synergistic Fenton employed on corncob in order to expose lignin content and saccharides to enhance the xylooligosaccharides yield by enzymatic hydrolysis. The dissolution of lignin and xylooligosaccharides production of corncob was enhanced by ultrasound assisted TiO 2 and Fenton reaction. The corncob pretreated with a sonocatalytic-synergistic Fenton reaction gave the highest release of the lignin concentration level (1.03 g/L), dissolution level (80.25%), and xylooligosaccharides content (46.45 mg/g substrate). A two-step pretreatment processes consisting of the alkali treatment (pretreatment) and sonocatalytic-synergistic Fenton process (posttreatment) illustrated that subsequent enzymatic hydrolysis could be enhanced considerably. The release of the lignin concentration and xylooligosaccharides content were 33.20 g/L and 174.81 mg/g substrate, respectively. The antioxidant potential of xylooligosaccharides showed significant differences regarding the amount of xylooligosaccharides and the phenolic compounds produced.